Complicaciones oculares asociadas al implante de lentes intraoculares fáquicos (2022)
Purpose: To describe the ocular complications associated with the implantation of phakic intraocular lenses in the different ametropias in adult patients through a review of the literature. Methods: a review of the literature was carried out, where databases such as Scopus, Pubmed, ScienceDirect and Scielo were reviewed, human studies published between 2018 and 2022. Results: intraocular lens implantation brings complications such as loss of endothelial cells, decreased intraocular pressure (IOP), changes in the trabecular meshwork, advanced pigment dispersion glaucoma, macular hole, traumatic aniridia or retinal detachment in myopic patients. and cataract. Conclusions: The implantation of an IOL is a good treatment option with a high percentage of success rate and a very low rate of ocular complications after its implantation, however, the loss of endothelial cells in implants of IOL of the anterior chamber is a of the most frequent complications and in posterior chamber implants, the most frequent complication was the production of cataracts.